(3eLed GddZIs - (3GHf aGQS , CHh GdMSjf CMeO Hf aGQS Hf RcQjGA GdbRhjfj GdQGRj,J (B395 (3g` s
(3ChdgG (B:s
(3HGH GdaGA heG HYOgG ai GdeVGYa hGdeWGHb (B: (3jbGd (B: (3QLd abaGb , hgh GdCMeb GdeNdW ai cdGeg s
(3GdfSNI ebGHdIs
(3cJHJ dCHi GdNjQ fUQ Hf Ydi Hf fUQ Hf GdMSjf GdCROis
(3fSNI YGTQI jJab BNQgG eY fSNI (B[ (3GdeJMa GdYQGbi (B- (3HZOGO (B542 ] (3HGNJdGa ai HYV GdLed hGdYHGQGJ hGdeaQOGJs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs